LIFE-HISTORY TRAITS OF Stethorus gilvifrons (MULSANT) (Coleoptera: Coccinellidae) ON PHYTOPHAGOUS MITES Eutetranychus orientalis KLEIN (Acari : Tetranychidae) - Handoko Handoko; Affandi Affandi (AGRIVITA, Journal of Agricultural Science, 2012)
The research aims to know the life cycle, feeding and mating behavior of predatory beetle S.  gilvifrons, and was conducted at entomology laboratory of Assessment Institute for agri-cultural technology Malang - East Java. The treatments involved feeding behavior and capacity of the various instars and imago of S. gilvifrons. The number of mites consumed within 24 hours by each stage of beetle was also recorded. The average voracity of five individual predators for each instar was determined.  The result showed that average life cycle of S.  gilvifrons feed on E. orientalis was 4.11 + 0.78; 8 + 1.10; 3.83 + 0.41, respectively for egg, larva and pupa.  The predator caught the preys from the front side, then chewed and sucked the body contents of adult preys or consumed the whole egg.  The feeding capacity was greater in egg-laying than that in non egg-laying females and males.  The smallest size of the cage (1.5 cm diameter x 5 cm long) and clear weather were the most preferred situation for S.  gilvifrons mating, which  usually occurs on the upper leaf surface.  The male positioned itself over the female body and extended its aedeagus to reach the female.    Keywords: Life-history, Stethorus gilvifrons, phytophagous mites